Identification of micronutrients deficiencies in five lowland soils from the cerrado region of Minas Gerais - Abreu, Cleide Aparecida de; Lopes, Alfredo Scheid; Andrade, Diva de Souza (Pesquisa Agropecuaria Brasileira, 2014)
Few data concerning micronutrient problems are available in lowland soils of Brazil, fact that justified this work with the following objectives: a) evaluate deficiencies of micronutrients determining the relative importance of these deficiencies; b) evaluate the reduction of natural soil fertility in relation to micronutrients, through four successive corn (Zea mays L.) croppings. The soil materials were Humic Gley (GH), Low Humic Gley (GPH) and Organic (ORG) from Uberaba, Minas Gerais State, Brazil, and Aluvial (AL) and Humic Gley (GH) from Careaçu, Minas Gerais State, Brazil with the following treatments: natural soil, complete; complete minus one micronutrients each time, and complete minus micronutrients plus FTE-BR 15. Considering the accumulative top dry mather yields for the four consecutive crops, it was observed that only the omission of Zn led yield depression and only in the HGC. For the first cropping depressions in yield were observed by omission of Zn in the GH and by addition of FTE-BR 15 in the AL and GH. Deficiencies observed for the first cropping were attenuated in the fourth cropping. These data justify the necessity of adequate evaluation of micronutrient availability in these soils, before making generalizations in preventing and/or correcting micronutrients problems.